2016
DOI: 10.1002/adem.201600474
|View full text |Cite
|
Sign up to set email alerts
|

High Strain Rate Tensile and Compressive Testing and Performance of Mesoporous Invar (FeNi36) Matrix Syntactic Foams Produced by Feedstock Extrusion

Abstract: The present study investigates the high strain rate behavior of mesoporous metal matrix syntactic foams focusing on the dependence of compressive and tensile properties on strain rate. The strain rate range, covered both in compression and tension, extends from quasi-static conditions or 10 À3 s À1 to 10 3 s À1 . Syntactic foams based on commercial high strength hollow glass microspheres and Invar (FeNi36) matrix are produced by means of feedstock extrusion and subsequent sintering. Levels of glass microsphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…Further, the microstructural study of MgMSFs showed grain refinement of the matrix with the progressive addition of the GMB hollow particles. Grain refinement in materials with the addition of nonmetallic particles was also reported by Peroni et al [45]. Nonmetallic particles-the hollow glass spheres as in this case-are known to restrict grain boundary movement in the metal matrix and, therefore, grain growth during sintering.…”
Section: Mechanical Propertiessupporting
confidence: 68%
“…Further, the microstructural study of MgMSFs showed grain refinement of the matrix with the progressive addition of the GMB hollow particles. Grain refinement in materials with the addition of nonmetallic particles was also reported by Peroni et al [45]. Nonmetallic particles-the hollow glass spheres as in this case-are known to restrict grain boundary movement in the metal matrix and, therefore, grain growth during sintering.…”
Section: Mechanical Propertiessupporting
confidence: 68%
“…Most processes investigated so far limit the effective range of porosities to an approximate maximum at around 50%. At the same time, several publications point at the fact that properties specifically under tensile load could benefit from improved interface strength between matrix and hollow particle, which is typically not achieved today [4,5]. The present study reverses the usual processing sequence by creating the interface between metal phase and hollow particles first and consolidating the resulting particles to form macroscopic bodies afterwards.…”
Section: Introductionmentioning
confidence: 77%
“…The demand for highly durable lightweight materials in the production of wear and corrosion-resistant components for reliable applications in the construction of aircrafts, cars, trains, ships, and military defence equipment has become critically high for market capacity. Researchers working on almost every type of materials are looking for a better combination of properties, e.g., the highest payload/density ratio: polymers and composites [3][4][5], metal matrix composites (iron-based [6][7][8][9]; steel-based [10,11]; Mg-based [12][13][14]); metalceramics [15][16][17][18]; ceramics and composites [19][20][21][22][23][24]; bio-based and hybrid materials [15,25].…”
Section: Introductionmentioning
confidence: 99%